The road to conscious machines : the story of AI / Michael Wooldridge. - Wooldridge, Michael J., 1966- (Pelican Books, 2020)
The ultimate dream of artificial intelligence is to build machines that are like us: conscious and self-aware. While this remains a remote possibility, rapid progress on AI in this century is already profoundly changing our world. Yet the public debate and media hype is still largely centred on unlikely prospects from sentient machines to dystopian robot takeovers. In this lively and clear-headed guide, Michael Wooldridge brings a healthy injection of humility to an overhyped field and changes the prevailing narrative on AI, revealing how these anxieties distract us from the more immediate risks that this transformative technology poses - from algorithmic bias to fake news.